Precursor-directed production of water-soluble red Monascus pigments with high thermal stability via azaphilic addition reaction-based semi-synthesis - He, Linman; Liu, Cai; Chen, Suo; Zhang, Jialan; Gao, Mengxiang; Li, Li (Food Chemistry: X, 2023)
[Display omitted] •A novel, attractive approach for preparing highly pure precursors of red MPs was developed.•The sufficient pure precursors enabled large-scale semi-synthesis of various red MPs congeners.•Most of the red MPs congeners exhibited improved water solubility, pH and thermal stability.•Red MPs congeners with the greatest thermal resistance were firstly identified.•The highly thermal resistant red MPs congeners were effective as colorants in liquid food formulations. Red Monascus pigments (MPs) are a large group of polyketides from the fungus Monascus which have been widely used as food colorants. In this study, a variety of red MPs congeners were prepared to explore promising water-soluble candidates for application in liquid food formulations. The results showed that by combining the two-stage, low-pH fermentation strategy with a downstream purification step of fractional crystallization, precursors of red MPs, namely monascorubrin and rubropunctatin, were obtained with a purity of 91.9%. Then, via the azaphilic addition reaction, 18 types of red MPs congeners carrying different amino acid moieties (MPs-aa) were semi-synthesized. Compared to rubropunctamine and monascorubramine, the water solubility, pH and thermal stability of MPs-aa were improved greatly. MPs-His, MPs-Phe, MPs-Tyr and MPs-Trp were identified to be the most resistant to pasteurization. These findings provide water-soluble red MPs candidates with high thermal stability and an attractive approach for their large scale production.